Dr. Aida García — Deep Plane Facelift — Madrid - García, Aida (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Aida García, practicing in Madrid, Spain. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003368; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; spain; madrid